Menino, quem foi teu mestre? A formação do mestre e a capoeira de Pelotas - Fonseca, Andre Oreques (2010)
The capoeira, a Brazilian immaterial cultural patrimony, Is enchanting thousands of people worldwide. Apprentices in more than 150 countries that make use of an entire range of possibilities and corporal and partner-cultural attractions linked to the capoeiragem. These attractions, quite peculiar, are responsible for the construction of a philosophy of a single life, which frames and mixes to the daily of its followers. Inside of this context the " master's " figure appears as the main responsible for preserving and spreading such singularities, such philosophy. And in the intention of unmasking some secrets of the process of these masters' formation is that the objectives of this work were structured, where, in a cartographic referential, four masters' formative processes of the city of Pelotas-RS were investigated. In a first moment, a bibliographical research to understand the nuances in relation to the master's formation since the beginning of the century XX to the current days was made. Soon after, the masters' of Pelotas accounts were colected, following the script of a semi-structured interview. This way it was possible to have a larger understanding concerning the intrigues of the capoeiragem, in the subject of the master's formation, as well as on the history of the capoeira in Pelotas and the constitution of this Capoeirano lifestyle